The Relationship between Premature Membrane Rupture and Neonatal Asphyxia at Gunung Jati Regional Hospital, Cirebon City - Muslicha, Ika; Mutya Sari, Vianty; Rahmatika, Siti Difta; Wiwin, Wiwin (Ann Publisher, 2024)
One significant risk factor associated with the occurrence of Premature Rupture of Membranes (PROM) is Neonatal Asphyxia. Premature rupture of membranes is a condition where the amniotic membrane breaks before the onset of labor, which can lead to infections and other complications, including asphyxia in newborns. According to several studies, the incidence of PROM ranges from 2% to 20% of all pregnancies, with the incidence varying depending on various factors, including access to healthcare services and the medical conditions of pregnant women. Neonatal asphyxia is a condition where a newborn baby experiences a lack of oxygen (hypoxia) that can lead to permanent organ damage or death. This study aims to determine the relationship between the incidence of Premature Rupture of Membranes (PROM) and the incidence of Neonatal Asphyxia at Gunung Jati Regional Hospital, Cirebon City in 2024.This research is a type of descriptive-analytical study, using the cross-sectional method. The population in this study consists of all deliveries recorded in the medical records of Gunung Jati Regional Hospital, Cirebon City for the period of January-April 2024, totaling 365. The sampling technique in this study is proportionate purposive random sampling taken from deliveries during the period of January-April 2024, amounting to 100 samples. The research results showed an incidence rate of Premature Rupture of Membranes (PROM) at Gunung Jati Regional Hospital, Cirebon City during the period of January–April 2024, with 53 cases (53%), an incidence rate of Asphyxia with 88 cases (88%), and a p-value of 0.017, which is less than 0.05. The conclusion of this study shows that the number of respondents who experienced PROM and asphyxia was 51 people (51%). The chi-square test results showed a significance value of 0.017 (p-value <0.05) and an Odds Ratio (OR) value of 6.892. From this study, it was found that there is a relationship between the incidence of premature rupture of membranes and the incidence of neonatal asphyxia at Gunung Jati Regional Hospital, Cirebon City during the period of January-April 2024.